Power supply for smart contact lens 2 - Yap, Wei Liang (Nanyang Technological University, 2024)
The advancement of smart contact lenses (SCL) has been increasingly popular in recent years. Global-tech companies have come out with initiatives, for example, overlaying information onto the real world and even detecting blood glucose levels from our tears. These are the potentials features in a SCLs. Consequently, all these projects require a power supply system to sustain itself and currently lithium-ion battery are being implemented in SCLs. However, lithium-ion battery is unsafe for human eye usage and alternatives such as using Polymerized hydrogel is introduced to act as power supply system. To build a safe power supply system, Polymerized hydrogels such as Copper Hexacyanoferrate (CuHCFe) and Prussian Blue (PB) are utilized and act as cathode and anode respectively. This allows the charging and discharging of ions within human tears which ultimately charges up the contact lens. In this project, the contact lens battery using PB and CuHCFe electrodes has been fabricated and evaluated on its electrochemical properties using Cyclic Voltammetry (CV) and Galvanostatic Cycling with Potential Limitations (GCPL) test. The result of the fabricated battery, tested with tear solution, gave desired results with average battery storage capacity of 0.132 mAh.